Study on the Quality of Water in the Bhavani River - GOPALSWAMI, P.M.; KUMAR, P.E.; KULANDAIVELU, A.R. (Asian Journal of Chemistry, 2010)
With a view to create awareness among the public about the quality of water in the Bhavani River, which is one of the important rivers of Tamilnadu, this study has been undertaken. The samples of water have been collected at various points along the course of the Bhavani river from the Nilgiris to Bhavani Kuduthurai. The samples of water were collected using standard procedural methods. The physiochemical analysis and biological examinations were extensively carried out on each sample using known standard methods. The results of these analyses point out the fact that the Bhavani river water is being highly polluted by letting out industrial effluents, industrial waste water, agricultural run off and sewage into the stream. The presence of inorganic ions such as hexavalent chromium, sulphate ions, etc., and biological waste has contributed to the pollution of the river water. As a result water borne diseases have become common in this area and the raw water cannot be used as such for industrial purposes. The Bhavani river water should be treated properly and disinfected before being supplied for industrial purposes and human consumption.